Familial pericentric inversion of chromosome 1 (p34q23) and male infertility with stage specific spermatogenic arrest. Issue 7 (July 1994) - Meschede, D; Froster, U G; Bergmann, M; Nieschlag, E
Abstract : We report on two infertile brothers presenting with severe oligozoospermia or azoospermia. Testicular biopsy was performed on one of them and showed spermatogenic arrest at the level of primary spermatocytes. Both brothers were found to be heterozygous for a pericentric inversion of chromosome 1 (46, XY, inv(1)(p34q23)). The inversion chromosome was inherited through the maternal line, with no indication of subfertility in the probands' mother.